Um der türkischen Sprache willen: Sadri Maksudi Arsal und seine Beiträge zur kemalistischen Sprachreform - Scherberger, Max Gustav (Ergon-Verlag, 2023)
This study analyses one of the major works of Kemalist language reform (Türk Dili için). It offers a key to understanding the purism that characterised Turkish language policy in the 1930s and 1940s and had a lasting impact on the modern Turkish language. It is written by the Tatar-Turkish intellectual Sadri Maksudi Arsal (d. 1957), who was one of the pioneers of modern Turkey, not only in the field of language, but also in the fields of history and law. This study examines the language, content, intellectual and historical background and impact of the work in the then nascent Turkish Republic.